Identifikasi senyawa bioaktif ekstrak metanol sereh wangi (cymbopogon nardus) dengan menggunakan gas chromatography-mass spectrometer - Simbolon, Gladys Renata; Donn R. Ricky (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The need for essential oils is increasing along with the increasing development of modern industries such as the perfume, cosmetic, pharmaceutical, food, aromatherapy and drug industries (Ella et al, 2013). Citronella is processed and processed to obtain pure essential oil so that it gets a high selling value, and research is carried out to identify GC-MS using 100 grams of citronella extract with the extraction process using 500 ml of methol solvent and evaporated for 25 minutes at 60°C. The results of GC-MS got the components from the highest to the lowest, namely the highest compound was hydroxymethyl of 33.40% with a retention of 6,500 minutes, the second highest compound was nonadecane of 29.47% with a retention of 23,559 minutes, the third highest compound was dodecanoic of 14.51 with a retention of 22.863 minutes, the fourth compound was pyran. of 13.31 with a retention of 5.333 minutes, and the lowest compound is dodecanoic of 9.31 with a retention of 23,333 minutes. From the results of the identification test of citronella extract using methanol as a solvent, the highest compound component is the hydroxymethyl group, this compound has several functions, namely, as an antioxidant and anti-microbial.